Social media and community knowledge: An ideal partnership for non‐profit organizations. Issue 1 (2013) - Given, Lisa M.; Forcier, Eric; Rathi, Dinesh
Abstract: Non‐profit organizations (NPOs) must manage knowledge to be relevant, sustainable and competitive. The published literature suggests that stories can be effective for sharing knowledge and making tacit knowledge explicit; however, researchers have not examined storytelling as a knowledge management practice in NPOs in any depth. Similarly, few studies explore the roles of social media in NPOs, including their usefulness for knowledge management practices. This paper reports the results of a research study that examined how NPOs are using social media, with a particular focus on knowledge management practices. Qualitative interviews with 16 staff members working in a range of NPO environments (such as health, library and social services organizations) were conducted. The findings point to the value of storytelling for sharing the organization's mission, for monitoring the NPOs reach into the community, and as a mechanism for gathering knowledge from clients and other key stakeholders.